Mengevaluasi Efektivitas Teknologi Pembelajaran Jarak Jauh Berdasarkan Kriteria Pedagogis dan Teknis - Ristiyanto, Tri Wahyu; Holilah, Enong; Suswasarosa, Asep Osa; Hakim, Lukmanul; Hasani, Aceng (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to evaluate the effectiveness of distance learning technology based on pedagogical and technical criteria. Using a literature review approach, the research analyzes previous studies to identify key factors that contribute to the success or failure of technology-based distance education. From the pedagogical perspective, the study highlights the importance of meaningful teacher-student interaction, adaptive teaching strategies, active student participation, and timely, constructive feedback. From the technical perspective, the study addresses access to infrastructure, system reliability, user interface design, and the availability of technical support. The findings reveal that distance learning is most effective when pedagogical design is supported by accessible, reliable, and user-friendly technology. A well-integrated approach combining synchronous and asynchronous learning methods enhances student engagement and learning outcomes. The study concludes that the impact of distance learning technologies depends not only on digital access but also on how thoughtfully those technologies are implemented within instructional frameworks. This research contributes to the development of more effective digital learning environments and provides practical insights for educators, policymakers, and education technology developers.